Generalized nonlinear variational inequality problems involving multivalued mappings. (1997) - Verma, Ram U.
Abstract : The solvability of a class of generalized nonlinear variational inequality problems involving multivalued, strongly monotone and strongly Lipschitz (a special type) operators, which are closely associated with generalized nonlinear complementarily problems, is discussed.